Perancangan Skema Dual Port Injection Sistem Electric Control Unit Motor Spark Ignition - Syarifudin; Kusnadi; Eflita Yohana; Suhartana; Faqih Fatkhurrozak; Firman Lukman Sanjaya (P3M Politeknik Negeri Cilacap, 2024)
Blending fuels is an urgent alternative to reduce dependence on gasoline. Blending gasoline-alcohol bioethanol is realistic due to its high octane number properties and the abundant availability of raw materials. However, high viscosity results in inconsistent fuel mixing homogenization and decreased injector performance. The research aims to design a Dual Port Injection scheme as a dummy simulation of fuel blending so that bioethanol alcohol can be homogeneously blended with gasoline in the combustion chamber. The method used is observation of the Electric Fuel Injection working system and designing a Dual Port Injection Scheme. The research resulted in a Dual Port Injection scheme with the concept of doubling the injection-based fuel system and commands from the commercial Electric Control Unit to be forwarded to the bioethanol and bioethanol fuel pumps to supply fuel to the high pressure pipe.